Plasma wakefield excitation providing homogeneous focusing of electron bunches - Maslov, V.I.; Onishchenko, I.N.; Yarovaya, I.P. (Вопросы атомной науки и техники, 2013)
Wakefield plasma lens, which focuses all relativistic electron bunches of the sequence identically and uniformly, are investigated analytically and by numerical simulation. The necessary conditions of such lens operation are the followings: length of the bunches is ξb=q(λ/2), q=1, 2, …(λ is the plasma wavelength), the distance between bunches is Δξ=pλ, p=1, 2, … All bunches have the same charge and the 1-st bunch has a half of this charge. It is shown that with the exception of 1-st bunch all other bunches are occurred in zero longitudinal wakefield and in uniform along bunch length focusing radial wakefield. In the case of inhomogeneous longitudinal distribution of electron bunch density the middle of bunches are focused slower in comparison with their edges. Аналитически и численным моделированием исследуется кильватерная плазменная линза, в которой все релятивистские электронные сгустки последовательности фокусируются одинаково и однородно. При этом необходимо, чтобы сгустки имели длины, равные ξb=q(λ/2), q=1, 2, …, скважность между сгустками была равна Δξ=pλ, p=1, 2,…, заряд 1-го сгустка был в два раза меньше зарядов всех остальных сгустков. Показано, что только 1-й сгусток находится в конечном продольном электрическом кильватерном поле Ez≠0. Другие сгустки находятся в Ez=0. Радиальная кильватерная сила Fr в областях расположения сгустков постоянна вдоль сгустков. В случае неоднородного продольного распределения плотности электронных сгустков их середины фокусируются медленнее, чем фронты. Аналітично і чисельним моделюванням досліджується кільватерна плазмова лінза, в якій усі релятивістські електронні згустки послідовності фокусуються однаково і однорідно. При цьому необхідно, щоб згустки мали довжини, рівні ξb=q(λ/2), q=1, 2, ..., шпаруватість між згустками була рівною Δξ=pλ, p=1, 2,…, заряд 1-го згустка був в два рази менше зарядів усіх інших згустків. Показано, що тільки 1-й згусток знаходиться в кінцевому поздовжньому кільватерному електричному полі Ez≠0. Інші згустки знаходяться в Ez=0. Радіальна кільватерна сила Fr в областях розташування згустків постійна уздовж згустків. У разі неоднорідного поздовжнього розподілу щільності електронних згустків їх середини фокусуються повільніше, ніж фронти.